Cooperative learning and personality types. (January 2016) - Emerson, Tisha L.N.; English, Linda; McGoldrick, KimMarie
Abstract: We examine whether student personality type helps explain differences in students' course perceptions across sections that varied only in the usage of cooperative learning. We use the Myers Briggs Type Indicator to classify students based on their preferred ways to take in information. We then compare the perceptions of students engaged in cooperative learning with perceptions of students engaged in independent problem-solving for each personality type. Despite the less positive impression of some personality types regarding cooperative learning activities, we find that these activities facilitated increased interaction among certain types of students who might not otherwise interact with classmates.